MAKNA PROFESI GURU, PROFESIONALISME, DAN KOMPETENSI YANG HARUS DIMILIKI GURU - Sabrina Putri Rahmani; Najwa Arni Mutari; Wina Aulia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Education is a fundamental aspect of improving the quality of human resources, with teachers serving as the primary actors in the learning process. However, there remains a gap between the ideal demands of teacher professionalism and the realities in practice, particularly in terms of competence and performance. This study aims to examine the concepts of profession, professionalism, and the competencies that teachers must possess to enhance the quality of education. The method employed is library research using a qualitative approach through the analysis of relevant scientific literature. The research stages include data collection, literature selection, content analysis, and conclusion drawing. The results indicate that teacher professionalism is closely related to competence, performance, and student learning outcomes. Professional teachers not only master subject matter but are also capable of managing classrooms, utilizing technology, and fostering student motivation. In addition, continuous professional development is a crucial factor in addressing the demands of education in the digital era. The study concludes that teacher professionalism is a key factor in improving educational quality; therefore, systematic efforts are needed through training, performance evaluation, and supportive educational policies to optimize the role of teachers as professionals. ABSTRAK Pendidikan merupakan aspek fundamental dalam meningkatkan kualitas sumber daya manusia, dengan guru sebagai aktor utama dalam proses pembelajaran. Namun, masih terdapat kesenjangan antara tuntutan profesionalisme guru yang ideal dengan kondisi nyata di lapangan, terutama dalam aspek kompetensi dan kinerja. Penelitian ini bertujuan untuk mengkaji makna profesi, profesionalisme, serta kompetensi yang harus dimiliki guru dalam upaya meningkatkan kualitas pendidikan. Metode yang digunakan adalah penelitian kepustakaan dengan pendekatan kualitatif melalui analisis berbagai literatur ilmiah yang relevan. Tahapan penelitian meliputi pengumpulan dan seleksi sumber, analisis isi, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa profesionalisme guru berkaitan erat dengan kompetensi, kinerja, dan hasil belajar siswa. Guru profesional tidak hanya menguasai materi pembelajaran, tetapi juga mampu mengelola kelas, memanfaatkan teknologi, serta membangun motivasi belajar siswa. Selain itu, pengembangan profesional secara berkelanjutan menjadi faktor penting dalam menghadapi tuntutan pembelajaran di era digital. Kesimpulan penelitian ini menegaskan bahwa profesionalisme guru merupakan kunci utama dalam peningkatan kualitas pendidikan, sehingga diperlukan upaya sistematis melalui pelatihan, evaluasi kinerja, dan dukungan kebijakan pendidikan.